A Raw Deal: Heightened Liberalism Following Exposure to Anomalous Playing Cards. (9th September 2013) - Proulx, Travis; Major, Brenda
Abstract : According to the meaning maintenance model, people may respond to meaning violations by affirming unrelated beliefs to which they are committed. While this affirmation generally moves in the direction of social inequality, meaning violations that are not personally threatening—but that nevertheless evoke uncertainty—should evoke a heightened preference for social equality (i.e., a socially liberal judgment). We tested this hypothesis in an experiment that exposed participants to reverse colored playing cards, where participants were subsequently more supportive of Affirmative Action if they were relatively committed to a belief that social inequality is unjust. This study demonstrates that people will make heightened socially liberal judgments following a meaning violation that is not personally threatening, and that is unrelated to the affirmed meaning frameworks.